Peony-Glycyrrhiza Decoction for Antipsychotic-Related Hyperprolactinemia in Women With Schizophrenia: A Randomized Controlled Trial. Issue 6 (December 2016) - Man, Sui Cheung; Li, Xian-Bin; Wang, Huai-Hai; Yuan, Hai-Ning; Wang, Hua-Ning; Zhang, Rui-Guo; Tan, Qing-Rong; Wong, Hei Kiu; McAlonan, Grainne M.; Wang, Chuan-Yue; Zhang, Zhang-Jin
Abstract : Objectives: An herbal preparation called peony-glycyrrhiza decoction (PGD) may have the potential in reducing antipsychotic-related hyperprolactinemia (hyperPRL). This double-blind, randomized placebo-controlled study aimed to reevaluate the efficacy of PGD against antipsychotic-related hyperPRL. Methods: Ninety-nine schizophrenic women who were under antipsychotic therapy and had symptomatic hyperPRL were randomly assigned to additional treatment with placebo (n = 50) or PGD (n = 49, 45 g/d) for 16 weeks. The severity of hyperPRL, psychosis, and abnormal involuntary movements was assessed at baseline and weeks 8 and 16 using standard instruments including the Prolactin Related Adverse Event Questionnaire. Blood levels of prolactin (PRL) and related pituitary and sex hormones were measured at the same time points. Results: Peony-glycyrrhiza decoction treatment produced a significantly greater reduction of the Prolactin Related Adverse Event Questionnaire score at weeks 8 and 16 and a greater improvement on abnormal involuntary movements at end point compared with placebo, without altering the severity of psychosis. The group treated with PGD showed significantly higher proportion of having overall improvement on hyperPRL symptoms (χ 2 = 4.010, P = 0.045) and menstrual resumption (χ 2 = 4.549, P = 0.033) at week 8 than placebo. Serum PRL levels were similar in the 2 groups. Conclusions: Peony-glycyrrhiza decoction is effective in reducing antipsychotic-related hyperPRL and abnormal involuntary movement symptoms, but no reduction in blood PRL concentrations was observed. The underlying mechanisms of PGD's effects need further investigation (trial registration of NCT01852331 atwww.clinicaltrials.gov ).